Subjective experience of the disease in patients with schizophrenia - Kaliksztein Fihman, Bertha (2001)
This descriptive investigation explores experimentation of the disease in 15 schizophrenic patients from the perspective of the patients themselves through semistructured interviews. The most significan! testimonies were the attribution of the disease to a lack of orientation from the parents, the perception of difficulties in learning and attention abilities in class and the scarce and conflictive interpersonal relationships. Having an occupation, psychological support and stability in their Ji ves were mentioned as aspects that contribute to significan! improvement. Feelings like fear, depression, lack of peace among others are inherent aspects of the disease. In our opinion listening to the patient helps to better understand the experiencing of schizophrenia.